Improving Student's Mathematics Understanding Ability on Two Variable Linear Equation System Materials by Using Problem Based Learning - Adelia Tasya; Usman Aripin (IKIP Siliwangi, 2021)
This study aims to find out the improvement of students' mathematics understanding ability on the material of the Two Variable Linear Equation System (SPLDV) with the application of problem-based learning (PBL). This type of research is classroom action research. This research was conducted on students of class X Multimedia in one of the Vocational High Schools in Cimahi City. At the beginning and end of learning students are given test questions. The subjects of this study were 15 students. In this study, the instrument used was 8 questions in the material for the Two Variable Linear Equation System (SPLDV) which focused more on the students' mathematical understanding ability regarding the material for the two-variable linear equation system.. The results of this study indicate that the aspects of students' mathematical understanding abilities have increased as seen from the questions tested in each test. Based on the results of the study, the authors concluded that the mathematical understanding ability of class X multimedia students of one of the Vocational High Schools in Cimahi City could be improved through problem-based learning.